Airway Basal Cells, Protectors of Epithelial Walls in Health and Respiratory Diseases - Ruysseveldt, Emma; Martens, Katleen; Steelant, Brecht (Frontiers in Allergy, 2021)
The airway epithelium provides a critical barrier to the outside environment. When its integrity is impaired, epithelial cells and residing immune cells collaborate to exclude pathogens and to heal tissue damage. Healing is achieved through tissue-specific stem cells: the airway basal cells. Positioned near the basal membrane, airway basal cells sense and respond to changes in tissue health by initiating a pro-inflammatory response and tissue repair via complex crosstalks with nearby fibroblasts and specialized immune cells. In addition, basal cells have the capacity to learn from previous encounters with the environment. Inflammation can indeed imprint a certain memory on basal cells by epigenetic changes so that sensitized tissues may respond differently to future assaults and the epithelium becomes better equipped to respond faster and more robustly to barrier defects. This memory can, however, be lost in diseased states. In this review, we discuss airway basal cells in respiratory diseases, the communication network between airway basal cells and tissue-resident and/or recruited immune cells, and how basal cell adaptation to environmental triggers occurs.